Genetic algorithm based approach to optimize phenotypical traits of virtual rice. (21st August 2016) - Ding, Weilong; Xu, Lifeng; Wei, Yang; Wu, Fuli; Zhu, Defeng; Zhang, Yuping; Max, Nelson
Abstract: How to select and combine good traits of rice to get high-production individuals is one of the key points in developing crop ideotype cultivation technologies. Existing cultivation methods for producing ideal plants, such as field trials and crop modeling, have some limits. In this paper, we propose a method based on a genetic algorithm (GA) and a functional-structural plant model (FSPM) to optimize plant types of virtual rice by dynamically adjusting phenotypical traits. In this algorithm, phenotypical traits such as leaf angles, plant heights, the maximum number of tiller, and the angle of tiller are considered as input parameters of our virtual rice model. We evaluate the photosynthetic output as a function of these parameters, and optimized them using a GA. This method has been implemented on GroIMP using the modeling language XL (eXtended L-System) and RGG (Relational Growth Grammar). A double haploid population of rice is adopted as test material in a case study. Our experimental results show that our method can not only optimize the parameters of rice plant type and increase the amount of light absorption, but can also significantly increase crop yield. Highlights: We report a method based on GA and FSPM model to optimize plant types of virtual rice. Phenotypical traits are considered as input parameters of our virtual rice model. The photosynthetic output is used to evaluate each individual plant type's quality. The experimental results explain the effectiveness of the proposed method.